2019
DOI: 10.1088/1361-6528/ab4507
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost, durable master molds for thermal-NIL, UV-NIL, and injection molding

Abstract: Mold cost and mold lifetime are essential concerns for mass production of micro/nano-patterned surfaces by nanoimprint lithography or micro/nanoinjection molding. Master molds are typically produced by subtractive processing using wafer-based clean room techniques. For imprint lithography, polymer copies of such molds can often be employed, but the durability of such molds is quite limited. The conditions of high temperature and pressure for injection molding require use of the durable masters created in stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…While nano-injection molding of structures as small as 25 nm has been reported in a thermoplastic, 41 most of the efforts on injection molding of nanostructures focused on fabrication of extended nanostructures for optical applications. [42][43][44][45][46][47][48] To use injection molding for nanofluidic applications, much tighter tolerances are needed to ensure the continuity of fluid transfer between nanoscale fluidic vias and microfluidic networks upon assembly of devices with a cover plate. Utko et al reported injection molding devices with arrays of extended nanochannels having 240 nm widths and 150 nm heights using cyclic olefin copolymer (COC) thermoplastic as the substrate and were used for the stretching of DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…While nano-injection molding of structures as small as 25 nm has been reported in a thermoplastic, 41 most of the efforts on injection molding of nanostructures focused on fabrication of extended nanostructures for optical applications. [42][43][44][45][46][47][48] To use injection molding for nanofluidic applications, much tighter tolerances are needed to ensure the continuity of fluid transfer between nanoscale fluidic vias and microfluidic networks upon assembly of devices with a cover plate. Utko et al reported injection molding devices with arrays of extended nanochannels having 240 nm widths and 150 nm heights using cyclic olefin copolymer (COC) thermoplastic as the substrate and were used for the stretching of DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The master molds are generally fabricated using focused ion beam lithography or electron beam lithography which are time-consuming and expensive processes [6][7][8]. Thus, the most expensive step in a complete NIL fabrication process is the fabrication of the master mold [9][10][11]. Since NIL is a 1:1 replication process, the resolution of the fabricated patterns depends on the resolution of the master mold.…”
Section: Introductionmentioning
confidence: 99%